Anxiety in the Structure of Journalist’s Integral Individuality - Bakhvalova, Alina (Bulletin of Taras Shevchenko National University of Kyiv. Psychology, 2021)
The article considers the place of anxiety in the journalist’s integral personality structure. Due to the difficulties and stress context of the journalist’s profession with deadlines, permanent urgency and sometimes even life dangerous anxiety may rise and its place in integral personality structure has not researched yet. More often, we may find publications about post-traumatic stress disorder syndrome among journalists than researches dedicated to anxiety, especially to its connections with other psychological properties and traits. Our purpose is to find the place of anxiety in the journalist’s integral personality structure. Reaching of purpose is reflected in the following tasks. The first task is establishing connections of anxiety with other individual psychological properties, the second, identifying predictors of anxiety and statistically prove their impact on the anxiety development, the third, establishing the links between anxiety and an integral characteristic of the individual which is professional self-esteem. The methods of this research are psychodiagnostic tests such as Structure of Temperament Questionnaire by Rusalov, Sixteen Personality Factor Questionnaire, Personality Value Orientations Questionnaire by Bubnova etc. The results of our research show anxiety has many links to temperament, psychological traits, and even values. Some of them are positive (emotionality, social emotionality, vigilance, tension, values of rest and respect), others are negative (ergic, plasticity, emotional stability, dominance, social boldness, perfectionism). Moreover, anxiety has causal relationships with other properties of psychological level (emotional stability, dominance, social boldness etc.). The influence of anxiety on personality was shown with an inverse statistically significant correlation between anxiety and professional self-esteem, which is an integral characteristic of individuality. This result reflects a need for socio-psychological or soft skills training that helps journalists to improve their professional self-esteem and to reduce the level of anxiety.